Hydrological evidence to guide climate resilient agricultural policies in Senegal - Cohard, Jean-Martial; Vandervaere, J.P. (CGIAR FOCUS Climate Security, 2022)
Many agricultural and land conservation programmes could use the latest hydrological evidence and methodology at early stages of programme design to improve long-term climate resilience and sustainability in Sahel region. This report presents stakeholder consultation, awareness (e.g., World Water Forum) and interdisciplinary research conducted in 2022 in Senegal. We evaluate the impact of bench terracing on water recharge and vegetation resilience to drought using satellite NDVI data and AMMA Catch long-term hydroclimate observatory datasets across 34 land conservation sites, covering 6600ha (period 2018-2021). Results show positive impacts from bench terracing but important variability. The causes of variability need to be determined to guide climate adaptation and land restoration.